Pengaturan yang Tepat atas Merek Kolektif untuk UMKM Berdasarkan Kepastian Hukum: Studi Perbandingan dengan Brasil - Audiya Dewi Rachmawati; Rika Ratna Permata; Laina Rafianti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Collective trademarks can be an alternative for trademark protection for Micro, Small, and Medium Enterprises (MSMEs) considering the greater benefits compared to regular trademarks. In 2024, there was an increase in the number of collective trademark applications, indicating that the public, especially MSMEs, are becoming more aware of the importance of trademark protection. However, issues have been found in the legislation regarding collective trademarks. This article aims to formulate the appropriate arrangements of collective trademark legislation that align with the MSME climate in Indonesia to achieve legal certainty. The research method used is normative juridical with a statutory approach, a conceptual approach, and a comparative approach. The regulation of collective trademarks in Indonesia will be compared with Brazil based on Law No. 9.279 of May 14, 1996, as amended by Law No. 14.200 of September 2, 2021. This research found that Law Number 20 of 2016 still contains several issues, namely the ambiguity of norms and articles that lead to multiple interpretations among the public. The provisions on collective trademarks in the Regulation of the Minister of Law and Human Rights Number 67 of 2016 (MIG Law) regulate substance similar to that stated in the MIG Law, whereas it should provide a more detailed and technical explanation. On the other hand, Law Number 15 of 2001, which was the previous regulation before the enactment of the MIG Law, provides a more comprehensive regulation on collective trademarks compared to the MIG Law. Thus, the legislation regarding collective trademarks does not yet provide legal certainty. The comparison with Brazil provides recommendations for appropriate arrangements, indicating the need for revisions and improvements to the legislation on collective trademarks to meet the need for more adequate regulations.